2020
DOI: 10.1002/jor.24788
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hip capsule morphology with patient symptoms from femoroacetabular impingement

Abstract: The relationship between morphological characteristics of the hip capsule and patient symptoms in the setting of femoroacetabular impingement (FAI) is undefined. In this study, patients with symptomatic FAI prospectively underwent 3T magnetic resonance (MR) imaging of the affected hip and completed the hip disability and osteoarthritis outcome score (HOOS) to determine the correlation between hip capsule anatomy and patient symptoms. Anterior hip capsule volume, posterior capsule volume, anterior‐posterior cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…At present, the influence of capsule healing and characteristics on the clinical outcomes of hip arthroscopy for treatment of FAI is still unknown. Shaw et al evaluated 35 patients with symptomatic FAI and concluded that increased anterior capsular volume is associated with greater preoperative pain [ 13 ]. However, this study did not mention postoperative PROs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the influence of capsule healing and characteristics on the clinical outcomes of hip arthroscopy for treatment of FAI is still unknown. Shaw et al evaluated 35 patients with symptomatic FAI and concluded that increased anterior capsular volume is associated with greater preoperative pain [ 13 ]. However, this study did not mention postoperative PROs.…”
Section: Discussionmentioning
confidence: 99%
“…The iliofemoral ligament is the strongest of the ligaments comprising the hip capsule and plays a significant role in hip stability [ 11 , 12 ]. Shaw et al found that hip capsule morphology correlates with patient symptoms in the setting of femoroacetabular impingement (FAI) as increased anterior capsular volume is associated with greater patient pain [ 13 ]. Nguyen et al thought changes in hip capsule morphology including decreased anterior–posterior capsule thickness ratio after surgery may be correlated with improvements in patient pain, function, and ability to return to sports [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The labro-capsular distance is the perpendicular distance between the line 3-4 and the point of the inferior labrum with the highest concavity [14]. need to be considered, which has shown promising results in hip instability [10,23]. For instance, Kay et al reported that capsular thinning correlates with anterior hip instability, making this a promising quantitative marker to implement in the study of capsular pathology for the unstable shoulder [10].…”
Section: Discussionmentioning
confidence: 99%
“…The joint capsule also plays a crucial role in various biological functions, and its morphology and dimensions to some extent indicate the severity of a patient’s condition [ 3 5 ]. Furthermore, arthroscopic surgery is a commonly employed minimally invasive technique in clinical practice for treating various conditions.…”
Section: Introductionmentioning
confidence: 99%